Acupuncture techniques for COPD: a systematic review - Carles Fernández-Jané; Jordi Vilaró; Yutong Fei; Congcong Wang; Jianping Liu; Na Huang; Ruyu Xia; Xia Tian; Ruixue Hu; Lingzi Wen; Mingkun Yu; Natàlia Gómara-Toldrà; et al. (BMC, 2020)
Abstract Background This is the second part of a large spectrum systematic review which aims to identify and assess the evidence for the efficacy of non-pharmacological acupuncture techniques in the treatment of chronic obstructive pulmonary disease (COPD). The results of all techniques except for filiform needle are described in this publication. Methods Eleven different databases were screened for randomised controlled trials up to June 2019. Authors in pairs extracted the data and assessed the risk of bias independently. RevMan 5.3 software was used for the meta-analysis. Results Thirty-three trials met the inclusion criteria, which involved the follow techniques: AcuTENS (7 trials), moxibustion (11 trials), acupressure (7 trials), ear acupuncture (6 trials), acupressure and ear acupuncture combined (1 trial) and cupping (1 trial). Due to the great heterogeneity, only 7 meta-analysis could be performed (AcuTENS vs sham on quality of life and exercise capacity, acupressure vs no acupressure on quality of life and anxiety and ear acupuncture vs sham on FEV1 and FEV1/FVC) with only acupressure showing statistical differences for quality of life (SMD: -0.63 95%CI: − 0.88, − 0.39 I2 = 0%) and anxiety (HAM-A scale MD:-4.83 95%CI: − 5.71, − 3.94 I2 = 0%). Conclusions Overall, strong evidence in favour of any technique was not found. Acupressure could be beneficial for dyspnoea, quality of life and anxiety, but this is based on low quality trials. Further large well-designed randomised control trials are needed to elucidate the possible role of acupuncture techniques in the treatment of COPD. Trial registration PROSPERO (identifier: CRD42014015074 ).